Computational Analysis of Free Fall Motion with Air Friction Constraints (Impulse: Journal of Research and Innovation in Physics Education, 2024)
Free fall motion without initial velocity is a mechanical concept that can be analyzed using analytical, experimental, and computational methods. Free fall motion is difficult to analyze analytically if air friction is not neglected. The aim of this research is to explain computational free fall motion analysis procedures with air friction. Air friction disturbance in free fall motion is represented by the coefficient C which states the drag coefficient is time dependent. In this scientific study, the application used for computational analysis is IDE Spyder with various library support. With the help of this application, a significant difference in the output vmax and tmax is obtained between the two cases of free fall based on the interpretation of the graph that appears.
Keywords: free fall motion; air friction; IDE Spyder